Study of the relationship between psychoneurological and degenerative disorders in patients with pain dysfunction of the temporomandibular joints - Syroiishko, Маріанна Василівна (Actual Dentistry, 2024)
Summary: An increase in the prevalence of painful dysfunctions of the temporomandibular joints (TMD), which, according to the modern views of the theory of combined pathogenesis, has neuromuscular, occlusive-articulation, psychophysiological, psychoemotional, and ischemic components, up to 82-87% among the general applications of dental patients profile indicates the need for new scientific research in this direction. And the increase in manifestations of the phenomenon of pain and its diversity in TMJ dysfunctions indicates that traditional therapy remains insufficiently effective and needs correction and improvement. The aim of this study is to study and compare the nature and degree of psychoneurological and degenerative-dystrophic disorders in patients with TMJ pain dysfunction. is to study and compare the nature and degree of changes in the electromyographic activity of the main and auxiliary masticatory muscles in patients with restored dentition defects during prosthetics using analog and digital methods. Research materials and methods. The representative contingent of patients included 48 people, of which 11 (22.9%) patients were male, 37 (77.1%) patients were female. The analysis of the dental status of the patients was carried out according to the data of the standard clinical examination, the standard and author’s questionnaire, the abbreviated “Hamburg” examination. The patients were diagnosed with defects of the teeth and dental rows, complicated by increased wear of the hard tissues of the teeth, secondary deformations, traumatic occlusion, TMJ dysfunction and parafunction of the masticatory muscles. To assess the patient’s psychoneurological condition, we used diagnostic methods of autonomic dysfunction syndrome, including segmental dysfunction. The intensity of the pain syndrome was assessed using visual analog scales. Personal and situational anxiety and depression were assessed. We determined situational and personal anxiety in patients with diseases of the maxillofacial apparatus according to the Spielberger-Hanin test (State-Trait Anxiety Inventory _ STAI)/ the severity of depression according to the L. Radloff depression scale, to which items from the A. Beck and W. Zung questionnaires were attached. The results Violations of central autonomic regulation were detected in the examined patients and were manifested by headache, unmotivated prolonged subfebrileness and syncopal states without signs of convulsive readiness on the encephalogram during encephalography. Vegetative dystonia with a paroxysmal course was diagnosed in 9 (18.8%) patients, vaginulid paroxysmal disorders – in 3 (6.3%) patients. TMJ dysfunctions and impaired vegetative activity of the nervous system against the background of stressful situations create an activating and maladaptive effect on regulatory mechanisms. Thus, among the studied group of patients, depression was diagnosed in 39 (81.3%) patients, including: mild degree – 21 persons (43.8%), medium degree – 14 persons (29.2%), severe degree – 4 persons (8.3%). Conclusions. As a result of our research, the feasibility of using the proposed complex diagnostic program for the functional state of the dento-maxillary, postural and autonomic nervous system of patients for the integrative assessment of the relationship between occlusal disorders of the jaws and postural disorders and vegetative dysfunction in patients with pathology of the temporomandibular joints was proven and substantiated. A multidisciplinary approach to treatment contributed to effective and quick rehabilitation of patients with TMJ pain dysfunction. The need for the proposed rehabilitation measures is related to the creation of individual treatment and rehabilitation algorithms, which necessarily take in to account the state of manifestation of the patient’s dental pathology, his general somatic condition, psychoneurological status, age and the state of the musculoskeletal system as a whole. Keywords: temporomandibular joints, prosthetic dentistry, dentition defect, masticatory muscles, musculoskeletal system, psychoneurological condition, degenerative-dystrophic disorders, occlusion.